Validity and Reliability Test of Four-Meter Gait Speed on Six Meter Track for Indonesian Adults - Nury Nusdwinuringtyas; Tresia Fransiska; Peggy Sunarjo; Kevin Triangto; Sopiyudin Dahlan (Faculty of Medicine, Universitas Padjadjaran, 2021)
Walking is an essential component of daily life and studies have shown the growing number of clinicians performing walking tests in their daily practice. This study is aimed to assess the validity and reliability of the Four-Meter Gait Speed (4MGS) test for healthy Indonesian adults (Mongoloid race). Data collection were conducted at the Rehabilitation Department of Dr. Cipto Mangunkusumo General Hospital during the period of August 2016 to March 2017. Two observers and two trials were involved in measuring the gait speed in the 4MGS test with a 6 meter track. All accumulated data were analyzed for validity using the Bland-Altman test, while test re-test reliability was done using Cronbach's alpha for internal consistency. Sixty-one subjects were involved in this study. There were no significant differences in inter-trial comparison from both observers (P=0.262 and P=0.954). Similarly, intra-observer walking speed comparison in both trials were also not significantly different (P=0.117 and P=0.869). The intraclass correlation coefficient (ICC) value between the first and second tests from observer I was 0.839 (Cronbach Alpha,0.911) while the value for observer II was 0.902 (Cronbach Alpha, 0.948). The ICC value between observer I and II in the first trial was 0.906 (Cronbach Alpha, 0.950); whereas the second trial demonstrated a value of 0.890 (Cronbach Alpha, 0.941). Thus, the 6 meter track 4MGS has a good validity and reliability for healthy Indonesian adults. It is expected that the walking speed from this study can be used for Mongoloid race living in other countries and the 4MGS can become an alternative speed-based walk test, especially during COVID-19 pandemic, due to its practicality in measuring functional capacity in a shorter duration.